2013
DOI: 10.1007/s00247-013-2628-y
|View full text |Cite
|
Sign up to set email alerts
|

Imaging features of intravesical urachal cysts in children

Abstract: The purpose of this report is to expand the spectrum of urachal remnant anomalies to include these newly recognized intravesical urachal cysts, which are characterized on US by the presence of a thin-walled cyst along the midline anterosuperior aspect of the urinary bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Congenital urachal remnants, urachal cysts in particular, are typically described as being external to the bladder. Nevertheless, there are reported instances in which these cysts, located at the anterosuperior aspect of the bladder, have appeared as intravesical lesions, ballooning into the bladder lumen or discharging intravesically (88). When infected, urachal cysts can appear with a hypervascular and heterogeneous echotexture at US and have variable enhancement at cross-sectional imaging (Fig 15).…”
Section: Inflammatory or Nonneoplastic Lesion Misinterpreted As A Tumormentioning
confidence: 99%
“…Congenital urachal remnants, urachal cysts in particular, are typically described as being external to the bladder. Nevertheless, there are reported instances in which these cysts, located at the anterosuperior aspect of the bladder, have appeared as intravesical lesions, ballooning into the bladder lumen or discharging intravesically (88). When infected, urachal cysts can appear with a hypervascular and heterogeneous echotexture at US and have variable enhancement at cross-sectional imaging (Fig 15).…”
Section: Inflammatory or Nonneoplastic Lesion Misinterpreted As A Tumormentioning
confidence: 99%
“…There are still con icting opinions regarding therapeutic options for optimal UA management. Several authors suggest that asymptomatic incidentally diagnosed urachal anomalies are normal variants that don't need any intervention with a high chance for spontaneous resolution, regardless of UA type [2,7,8] . On the other hand, some argue that prophylactic surgery should be utilized in all patients in order to prevent progression to the symptomatic UA and further complications such as malignant transformation [5] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that urachal cyst is the most common type with 45% of cases, followed by urachal sinus with 37%, patent urachus in 16%, respectively [6] . There's no consensus about the urachal anomalies management approach [7,8] . Recent studies support the hypothesis that symptomatic and asymptomatic children will bene t from performing surgical excision with a bladder cuff because of the risk of malignant transformation [9] .…”
Section: Introductionmentioning
confidence: 99%
“…It is composed of three layers: modified transitional epithelium, fibroconnective tissue and a layer of smooth muscle continuous with the detrusor 10. Failure of the obliteration of the allantois gives rise to rare abnormalities such as the formation of URs: complete patent urachus with free communication between bladder and umbilicus, persistent tissue at umbilicus with no connection to the bladder (umbilical polyp), persistent tissue at bladder with no connection to umbilicus resulting in bladder diverticulum, patent mid-duct with closure forming urachal cyst 11. A patent urachus is found in 1 in 200 000 live births and 1 in 5000 adults have an urachal cyst at autopsy 12.…”
Section: Discussionmentioning
confidence: 99%